Prevalence of internet addiction and its association with quality of sleep among arts and science college students of Puducherry, India - Razik, Mohammed C. A.; Premarajan, Kariyarath Cheriyath; Sujiv, Akkilgunta; Olickal, Jeby Jose (International Journal Of Community Medicine And Public Health, 2021)
Background: College students are found to be heavy users of internet globally. Hence, present study was aimed to find the prevalence of internet addiction and the association of internet addiction with quality of sleep. Methods: An institution-based cross-sectional analytical study was conducted among arts and science college students of Puducherry, India. Two arts and science colleges selected and proportionate stratified sampling was used for selecting the students. Young’s internet addiction scale and Pittsburgh sleep quality index were used as study tools. Results: A total of 497 students participated in the study. The median age was 19 years, and 56.3% were males. The prevalence of mild internet addiction was 42% (95% CI 37.9-46.6), and moderate addiction was 18.7% (95% CI 15.5-22.3). Prevalence of poor sleep quality was 63% (95% CI 58.8-67.3). After adjusting for the covariates, male gender had high internet addictions (2.24 95% CI 1.84-2.72, p<0.001). Students with internet addiction had 1.67 times poor sleep quality compared to their counterparts (p<0.001). Students from 20 to 24 years had poor sleep quality compared to18-19 years (p=0.040). Conclusions: There was a high prevalence of poor sleep quality among college students and was associated with internet addiction.